Effectiveness of clindamycin-based exposure strategies in experimental mature staphylococcal biofilms - S. C. J. van Dun; M. Verheul; B. G. C. W. Pijls; H. Scheper; A. M. van der Does; P. H. Nibbering; M. G. J. de Boer (Microbiology Spectrum)
ABSTRACT Due to increasing antimicrobial resistance and side effects caused by current standard antimicrobial regimens used for treatment of prosthetic joint infection (PJI), alternative options are urgently needed. We aimed to investigate the effect of clindamycin in different exposure strategies against Staphylococcus aureus in an in vitro mature biofilm model. In short, 7-day biofilms were generated on polystyrene plates and titanium–aluminum–vanadium discs using a clinical S. aureus PJI isolate. Next, biofilms were exposed to clindamycin according to four strategies: single 24-h exposure; prolonged 48- or 72-h exposure; repeated 24-h exposures during a 4-day period, and sequential exposures of initial 24-h rifampicin-based therapy followed by 24-h exposure to clindamycin. The remaining bacterial load (colony-forming unit [CFU]/mL) after antibiotic exposure was assessed. Confocal laser scanning and atomic force microscopy were applied to evaluate the biofilm structure. Single exposure to clindamycin for 24 h or prolonged up to 72 h did not result in any relevant reduction in bacterial load. Repeated 24-h exposures demonstrated relevant reductions of >3 log CFU/mL at clindamycin concentrations ≥16 mg/L for the 3rd and 4th consecutive doses. Sequential rifampicin–ciprofloxacin combination exposure followed by clindamycin showed bacterial load reductions of 3- to 4-log CFU/mL, similar to continued rifampicin–ciprofloxacin exposure. This was achieved for concentrations equivalent to levels achieved after standard dosing of clindamycin in clinical practice. These experimental findings support that clindamycin monotherapy is not an optimal choice when starting antimicrobial treatment of PJI but that later on, rifampicin may be safely switched to clindamycin in patients with PJI who do not tolerate prolonged rifampicin-based treatment.IMPORTANCERifampicin—in combination with another antibiotics—is recommended in all guidelines as first choice treatment of prosthetic joint infections (PJIs), despite adverse interactions and side effects associated with this antibiotic. In a search for alternative approaches, the switch to clindamycin in patients after rifampicin-based antibiotic treatment was found to be effective in some recent observational clinical studies. In our in vitro study, we determined the effect of clindamycin on Staphylococcus aureus in mature biofilms, to obtain further insight. Our study showed that clindamycin was effective in reducing mature biofilm-residing S. aureus after initial exposure to rifampicin–ciprofloxacin, while it was not effective as first treatment. These in vitro findings provide evidence for the hypothesis that rifampicin–ciprofloxacin can be successfully switched to clindamycin monotherapy in PJI patients in a later phase of treatment.